2019
DOI: 10.1016/j.idcr.2019.e00613
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus pericarditis causing cardiac tamponade

Abstract: Community acquired methicillin-resistant Staphylococcus aureus (MRSA) is an organism that can cause life threatening injuries with 6 cases of purulent pericarditis secondary to MRSA being reported so far. We report a 66 year-old -female who presented to our hospital with a two-week history of worsening shortness of breath, associated with pleuritic chest pain and chills. Patient was found to be positive for influenza type A virus two weeks prior to this presentation, but was never treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Pericarditis due to MRSA is a rare event, only a handful of cases (12 patients) have been reported in the literature (Table 1). [6][7][8][9][10][11][12][13][14][15] Our review of literature revealed that patients across all age groups developed MRSA pericarditis (ranging from 7 months to 75 years). Direct spread from intrathoracic focus of infection (myocardial foci, thoracic surgery or contamination from penetrating trauma), hematogenous spread and extension from subdiaphragmatic suppurative focus are the various mechanisms described for the development of purulent pericarditis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pericarditis due to MRSA is a rare event, only a handful of cases (12 patients) have been reported in the literature (Table 1). [6][7][8][9][10][11][12][13][14][15] Our review of literature revealed that patients across all age groups developed MRSA pericarditis (ranging from 7 months to 75 years). Direct spread from intrathoracic focus of infection (myocardial foci, thoracic surgery or contamination from penetrating trauma), hematogenous spread and extension from subdiaphragmatic suppurative focus are the various mechanisms described for the development of purulent pericarditis.…”
Section: Discussionmentioning
confidence: 95%
“…11 Cardiac tamponade was documented in a total of 7 patients. [6][7][8][9][10]12,15 Our search results revealed that vancomycin was the most common antibiotic used for the treatment of MRSA pericarditis. Duration for antibiotics therapy was variable (ranging from 2 to 6 weeks, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This organism colonizes the nasopharynx, perineum, and skin, and it can migrate into the circulatory system and lead to hematogenous spread if the cutaneous barrier is disrupted or damaged. The diagnosis of purulent pericarditis from MRSA is extremely rare, with only a few case reports thus far [2][3][4][5][6][7][8]. However, the mortality rate for untreated patients can approach 100% but decreases to 40% in those patients who are appropriately treated with antibiotics and source control [9].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus was one of the causes of the death in several developing countries including Indonesia. 1,2 S. aureus infection is a serious problem today due to the increasing resistance of bacteria to various types of antibiotics (Multi Drug Resistance / MDR), such as MRSA (Methicillin Resistant S. aureus). There were six reported cases of purulent pericarditis due to MRSA in Jacksonville, Florida, USA in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…There were six reported cases of purulent pericarditis due to MRSA in Jacksonville, Florida, USA in 2019. 1 Another unusual case report in New Delhi, India in 2016 of fatal bacterial myocarditis in a seven year old girl, who had a history of cough for a month and fever for two days. Autopsy revealed pyogenic bacterial myocarditis associated with bilateral lobar pneumonia caused by gram positive cocci named S. aureus.…”
Section: Introductionmentioning
confidence: 99%